Empowering junior high school math teachers through CRT-based videoscribe materials to enhance teaching quality - Eka Rachma Kurniasi; Mercy Hermawati; Arfatin Nurrahmah; Azzahra Ramadhani; Zhofron Abdan Taqiyan (University of Merdeka Malang, 2025)
The limited involvement of local cultural contexts in mathematics learning results in a lack of connection between the learning material and students' daily lives. The partner in this community service program are members od the Mathematics Subject Teachers' Forum (MGMP) of Junior High Schools in the Central Region of Bogor Regenc. The objectives of this Community Service Program (PKM) activity are: (1) Improving the understanding and competency of mathematics teachers in the Central Region of Bogor Regency regarding the creation of CRT-based teaching materials using Videoscribe, through training, independent projects, mentoring, and sharing of good practices; (2) Increasing teacher productivity in creating interactive CRT-based teaching materials using Videoscribe; (3) Encouraging the implementation of CRT-based teaching materials using Videoscribe; (4) Improving the quality of mathematics learning. The community service methods include training, mentoring and evaluation, independent practice, and implementation. The result of this service is an increase in the level of empowerment of partners in understanding the CRT learning model with a post-test score of ≥75. 100 percent of partners are able to create CRT teaching materials with the help of videoscribe, and 75 percent apply it in class. and 50 percent share good practices of training materials with colleagues at their respective schools.